2010
DOI: 10.3324/haematol.2009.010843
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between minimal residual disease measured by multiparametric flow cytometry prior to allogeneic hematopoietic stem cell transplantation and outcome in children with acute lymphoblastic leukemia

Abstract: BackgroundThe presence of minimal residual disease detected by polymerase chain reaction techniques prior to allogeneic hematopoietic stem cell transplantation has proven to be an independent prognostic factor for poor outcome in children with acute lymphoblastic leukemia. Design and MethodsThe aim of this study was to ascertain whether the presence of minimal residual disease detected by multiparametric flow cytometry prior to allogeneic hematopoietic stem cell transplantation is related to outcome in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 30 publications
4
44
0
Order By: Relevance
“…To this date, the impact of MRD before transplantation in childhood ALL has only been addressed in studies with a relatively small number of patients. 19,26,27 In this study, including 170 patients with a median follow-up of 4 years, we have shown that MRD before UCBT is a strong predictive Leukemia Free Survival Figure 2. The estimated 4-year probability of LFS in children with ALL in remission by MRD status before UCBT.…”
Section: Discussionmentioning
confidence: 68%
“…To this date, the impact of MRD before transplantation in childhood ALL has only been addressed in studies with a relatively small number of patients. 19,26,27 In this study, including 170 patients with a median follow-up of 4 years, we have shown that MRD before UCBT is a strong predictive Leukemia Free Survival Figure 2. The estimated 4-year probability of LFS in children with ALL in remission by MRD status before UCBT.…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, these studies uniformly found excellent long-term outcomes for patients without detectable MRD (that is, 'MRD À ' patients) undergoing myeloablative AlloHCT, with 2-5 year estimates of EFS, relapse-free survival and OS often in the 70-80% range, and more recent series suggesting even better outcomes. [29][30][31][34][35][36][37][39][40][41][42][43][46][47][48][49] Almost without exception, the outcomes for patients with detectable MRD (that is, 'MRD þ ' patients) were significantly inferior, with long-term estimates of EFS of 0-30% and OS of 30-50%, respectively. Although data are more limited for AutoHCT, available information suggests that MRD À patients may have relatively good disease control that appears to approach that seen after AlloHCT, at least in the subset of leukemias that do not harbor the Philadelphia chromosome; on the other hand, MRD þ ALL patients experience exceedingly high rates of relapse after AutoHCT.…”
Section: The Concept and Determination Of Mrdmentioning
confidence: 99%
“…53,57,61,62 However, MRD appears to bear significance as an independent prognostic marker, as suggested by multivariate regression modeling in many of the studies. [27][28][29]36,37,39,[42][43][44][47][48][49]53,54,57,[59][60][61] The association between MRD and risk of BM relapse is likely 'dose-dependent' in ALL 27,28,36,37,41,42,44,47,63 and, possibly, AML, 53,54,60 while MRD assessments may fail to predict extramedullary relapse accurately. 32,45 Interestingly, evidence from logistic regression models suggests that the relative level of MRD has more impact on survival in ALL than in AML.…”
Section: The Concept and Determination Of Mrdmentioning
confidence: 99%
“…110,111,189 These studies have shown, to varying degrees, that MRD status prior to HSCT appears to be an important prognostic determinant of long-term RFS and OS, with MRD-negative (< 0.01% marrow blasts) patients experiencing superior survival compared with MRD-positive (> 0.01% to 5% marrow blasts) patients, including within studies of children with relapsed ALL. These data support the assumption of a continuous relationship between MRD level prior to HSCT and 5-year survival probability.…”
Section: Input Assumptionmentioning
confidence: 99%
“…Similar findings were reported in a study that included a slightly larger sample of those post second or later relapse (n = 18). 110 Based on these and other studies, there is the suggestion of benefits through MRD-directed therapies, although controlled trials are needed to define their value. 109 Immunotherapies are showing promise and are being investigated.…”
Section: Haematopoietic Stem Cell Transplantationmentioning
confidence: 99%